The Impact of User Experience on Consumer Well-Being Among Netflix Users - Yesi Safita; Alfansi, Lizar (Universitas Negeri Semarang, 2025)
This study aims to explore the influence of user experience on consumer well-being on Netflix. Consumers have many options in choosing entertainment content to watch on Netflix and choose content that has a positive impact on aspects of their lives so as to achieve consumer well-being. With the growing popularity of streaming services, this study focuses on factors such as self-image fit, convenience factor, functionality factor, brand loyalty, attachment to the brand community, and frequency of use. This study uses quantitative methods with multiple linear regression analysis, data collected through online surveys from Netflix users. The results showed that self-image conformity, convenience factor, functionality factor, brand loyalty, brand community attachment have a significant influence on consumer well-being variables while current consumption variables do not have a significant influence on consumer well-being variables. Future researchers are also in addition, future researchers are also advised to examine other factors related to consumer well-being.